Visible-light induced photosplitting of water using solution-processed Cu2BaSnS4 photoelectrodes and a tandem approach for development of Pt-free photoelectrochemical cell - Sharma, Akash; Sahoo, Pooja; Singha, Abhijit; Padhan, Subash; Thangavel, R. (Materials science in semiconductor processing, 2021)
In this present work, investigation on the physical and chemical properties of the quaternary Copper–barium–thiostannate (Cu2BaSnS4) compound was carried out. Cu2BaSnS4(CBTS) thin films were synthesized by using the cost-effective, sol-gel spin-coating technique without further sulfurization. The light-sensitive nature of CBTS was investigated by illuminating the thin films directly under AM 1.5G condition, resulting in an enhancement of 47% in terms of photocurrent density. The p-type nature was confirmed from the Mott Schottky analysis carried out in 0.5 M Na2Ssolution without illumination. A flat band potential value of 2.354 ±0.003 V vs. RHE along with a carrier density of 9.314 ×1019cm−3and Debye length of 0.288 nm were also obtained for the CBTS thin films. From Bode plots, the carrier lifetime of CBTS films was estimated to be 88 m s. Further Pt-free photoelectrochemical cells were fabricated by using ZnO nanorods as counter electrodes. From linear sweep voltammetry results, photocurrent density of −6.805 and −2.112 mA/cm2 at 0 V (vs. RHE) under illumination in the presence of Pt electrodes and ZnO Nanorods, respectively. Photoconversion efficiency of ∼10% and ∼4% were estimated for the CBTS thin film in the presence of Pt and ZnO counter electrodes. Thus the physical properties observed here indicate the suitability of solution-processed CBTS thin films in its further use for harvesting solar energy. [Display omitted] •A facile sulfurization free, solution-processed synthesis procedure was adopted for Cu2BaSnS4 was adopted.•We observe a significant enhancement of nearly 47% upon illumination, proving its credential as a photoabsorber.•The Pt-free photoelectrochemical cell resulted a photocurrent density of −2.112 mA/cm2 at 0 V (vs. RHE) under illumination.•CBTS thin films showed a photoconversion efficiency of ∼4% in presence of ZnO Nanorods as the counter electrode.